GE_GERICHTE P/1936/2011 vom 10. Mai 2011 - GE Cour de justice (2011)
; NOTIFICATION DE LA DÉCISION ; DOMICILE ÉLU ; DEVOIR D'ASSISTANCE(FAMILLE) ; ASSISTANCE JUDICIAIRE ; FRAIS DE LA PROCÉDURE | CPP.87; CPP.310; CPP.136; RAJ.20; RTMFP